2021
DOI: 10.1186/s13690-021-00712-2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, performance, and determinant factors of Vitamin D deficiency prevention behaviours among Iranian pregnant women

Abstract: Background Pregnancy is a high-risk period for vitamin D (Vit D) deficiency, and there is a direct relationship between Vit D deficiency during this period and maternal and fetal complications. Therefore, this study aimed to assess the knowledge, attitude, and practice of pregnant women concerning the adoption of behaviors to prevent Vit D deficiency and identify the determinant factors of such behaviors. Methods In this cross-sectional study, 185 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“… 74 Multiple studies suggest developing/improving an awareness program on vitamin D supplementation in public and healthcare professionals (HCPs) to reduce vitamin D deficiency in pregnant women. 75 77 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 74 Multiple studies suggest developing/improving an awareness program on vitamin D supplementation in public and healthcare professionals (HCPs) to reduce vitamin D deficiency in pregnant women. 75 77 …”
Section: Resultsmentioning
confidence: 99%
“…74 Multiple studies suggest developing/improving an awareness program on vitamin D supplementation in public and healthcare professionals (HCPs) to reduce vitamin D deficiency in pregnant women. [75][76][77] Iodine. During pregnancy, iodine requirement increases because of increased thyroid hormone production and iodine excretion.…”
Section: Nutritional Gaps and Strategies To Address Micronutrient Ins...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, previous research in the Arab world has identified a lack of general population knowledge and awareness regarding vitamin D deficiency, highlighting the need for educational programs to enhance awareness [ 15 , 16 ]. Several studies emphasize the critical role of acquiring appropriate knowledge in mitigating vitamin D deficiency and promoting overall health [ 17 ].…”
Section: Introductionmentioning
confidence: 99%